2010
DOI: 10.1159/000320877
|View full text |Cite
|
Sign up to set email alerts
|

HPV Test Results Stratify Risk for Histopathologic Follow-Up Findings of High-Grade Cervical Intra-Epithelial Neoplasia in Women with Low-Grade Squamous Intra-Epithelial Lesion Pap Results

Abstract: Objective: Age-adjusted evaluations have explored the possible utility of human papillomavirus (HPV) test results in women with low-grade squamous intra-epithelial lesion (LSIL) Paps. We document LSIL correlation data with HPV test results and histopathologic follow-up from a large academic women’s hospital practice. Study Design: LSIL Pap tests with intermediate-/high-risk HPV DNA testing between July 1, 2005 and April 30, 2008 were studied along with follow-up histopathologic diagnoses. Patients were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
5
17
0
Order By: Relevance
“…There was a clear decline in the HPV prevalence in older age groups. 11 These HPV prevalence data are slightly higher than the meta-analysis performed by Arbyn 12 (76.6%) but are still within the range of previously reported studies (58e85%). Ronco et al also reported that the hrHPV-positive rate was significantly higher in younger women, and that there was a statistically significant decrease in older age groups.…”
Section: Prevalence Of Hrhpv In Women With Lsil Cytologysupporting
confidence: 67%
See 3 more Smart Citations
“…There was a clear decline in the HPV prevalence in older age groups. 11 These HPV prevalence data are slightly higher than the meta-analysis performed by Arbyn 12 (76.6%) but are still within the range of previously reported studies (58e85%). Ronco et al also reported that the hrHPV-positive rate was significantly higher in younger women, and that there was a statistically significant decrease in older age groups.…”
Section: Prevalence Of Hrhpv In Women With Lsil Cytologysupporting
confidence: 67%
“…5 MWH's data indicated that 89 of 612 patients with HPV-positive LSIL (14.5%) had a follow-up histopathological diagnosis of CIN 2/3; only 4 of 107 (3.7%) patients with HPV-negative LSIL had CIN 2/3; no histopathological CIN 2/3 diagnoses were identified in women 50 years and older with HPV-negative LSIL. 11 HPV test results stratified women with LSIL cytology findings into lower and higher-risk groups for follow-up histopathologic CIN 2/3 outcomes. hrHPV testing is highly sensitive for detection of high grade cervical squamous lesions, with high NPV but limited specificity.…”
Section: Prevalence Of Hrhpv In Women With Lsil Cytologymentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation for this finding could be that the VAIN 1 lesions harbor low-risk HPV types that are not detected by the high-risk HC2 test. In one study, 33 performed on vaginal biopsies, 35% of patients with VAIN 1 tested positive for low-risk HPV types. Another possible explanation could be an overinterpretation of nonneoplastic, mild vaginal squamous atypia as VAIN 1.…”
Section: Commentmentioning
confidence: 99%